2003
DOI: 10.1086/345865
|View full text |Cite
|
Sign up to set email alerts
|

A 4‐Year Study of the Epidemiology ofVibrio choleraein Four Rural Areas of Bangladesh

Abstract: How Vibrio cholerae spreads around the world and what determines its seasonal peaks in endemic areas are not known. These features of cholera have been hypothesized to be primarily the result of environmental factors associated with aquatic habitats that can now be identified. Since 1997, fortnightly surveillance in 4 widely separated geographic locations in Bangladesh has been performed to identify patients with cholera and to collect environmental data. A total of 5670 patients (53% <5 years of age) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
133
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 21 publications
8
133
1
Order By: Relevance
“…Our results also indicate that S. flexneri is the dominant circulating species; this finding supports reports previously indicating the dominance of S. flexneri in Bangladesh [32]. The results from the study also illustrate that V. cholerae continues to be a major [33,34,35]. V. cholerae was the primary pathogen in four major flood-associated diarrhoeal epidemics that occurred in Dhaka, Bangladesh, in 1988Bangladesh, in , 1998Bangladesh, in , 2004Bangladesh, in , and 2007.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results also indicate that S. flexneri is the dominant circulating species; this finding supports reports previously indicating the dominance of S. flexneri in Bangladesh [32]. The results from the study also illustrate that V. cholerae continues to be a major [33,34,35]. V. cholerae was the primary pathogen in four major flood-associated diarrhoeal epidemics that occurred in Dhaka, Bangladesh, in 1988Bangladesh, in , 1998Bangladesh, in , 2004Bangladesh, in , and 2007.…”
Section: Discussionsupporting
confidence: 90%
“…Despite its prominence, variable isolation rates of V. cholerae were documented at the different surveillance sites, with Dhaka having the highest, where cholera accounted for 14% of diarrhoea cases. The results of a study conducted in rural Bangladesh also found much variation among isolation rate of V. cholerae [35].…”
Section: Discussionmentioning
confidence: 95%
“…Indeed for Kolkata, higher values of CHL ano reflected the more intense algal blooms than normal that occurred and led to larger zooplankton populations that were comprised mainly of crustacean copepods, a natural aquatic host for V. cholerae (1,8,9). From the analyses of the Dhaka, Bangladesh data, it was concluded that the tidal intrusion of coastal water carrying plankton into inland water could initiate increased human contact with the cholera vibrio (14), because water used for daily hygiene, personal consumption, and religious rites (e.g., ablu- tions) in rural areas of Bangladesh and India is taken directly from local rivers or ponds essentially untreated (13,23,24). The relationship observed for PRE ano similarly reflects the effect of unusually heavy precipitation influencing cholera transmission by feeding surface runoff into streams and rivers flooding the water supply (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of endemic cholera have relied largely on data aggregated over relatively large spatial scales (2,4,5) and statistical models for recurrent outbreaks in urban centers have so far achieved prediction at lead times of ≤1 mo (6, 7), too short to be of use in early warning systems. Studies have also shown that the El Niño southern oscillation (ENSO) influences multiannual cycles in disease incidence (4,2,8,9) but because such global climate drivers have been expected to act over large spatial scales and to synchronize epidemiological responses across space (the Moran effect) (10,11) and because the physical and ecological linkages between global drivers and local transmission remain obscure (12)(13)(14)16), the fine-scale spatiotemporal dynamics of endemic cholera have been largely ignored.…”
mentioning
confidence: 99%